The Clinical Features and Diagnosis of Canavan’s Disease: A Case Series of Iranian Patients - KARIMZADEH, Parvaneh; JAFARI, Narjes; NEJAD BIGLARI*, Habibe; RAHIMIAN, Elham; AHMADABADI, Farzad; NEMATI, Hamid; NASEHI, Mohamad Mehdi; GHOFRANI, Mohammad; MOLLAMOHAMMADI, Mohsen (Iranian Journal of Child Neurology, 2014)
<!--[if gte mso 9]> <![endif]--> How to Cite This Article: Karimzadeh P, Jafari N, Nejad Biglari H, Rahimian E, Ahmadabadi F, Nemati H, Nasehi MM, Ghofrani M, Mollamohammadi M. The Clinical Features and Diagnosis of Canavan’s Disease: A Case Series of Iranian Patients. Iran J Child Neurol. 2014 Autumn;8(3): 66-71. Abstract Objective Canavan’s disease is a lethal illness caused by a single gene mutation that is inherited as an autosomal recessive pattern. It has many different clinical features especially in the non-Ashkenazi Jewish population. Material & Methods 45 patients were referred to the Pediatric Neurology Department of Mofid Children’s Hospital in Tehran-Iran from 2010–2014 with a chief complaint of neuro developmental delays, seizures, and neuroimaging findings of leukodystrophy were included in this study. Magnetic Resonance Spectrometry (MRS) and neuro metabolic assessment from a referral laboratory in Germany confirmed that 17 patients had Canavan’s disease. Results Visual impairment, seizure, hypotonia, neuro developmental arrest, and macrocephaly were the most consistent findings in the patients in this study. Assessments of neuro developmental status revealed that 13 (76%) patients had neuro developmental delays and 4 (24%) patients had normal neuro development until 18 months of age and then their neuro developmental milestones regressed. In this study, 100% of cases had macrocephalia and 76% of these patients had visual impairment. A history of seizures was positive in 8 (47%) patients and began around 3 months of age with the most common type of seizure was tonic spasm. EEGs were abnormal in all epileptic patients. In ten of the infantile group, we did not detect elevated level of N-acetylaspartic acid (NAA) in serum and urine. However, the MRS showed typical findings for Canavan’s disease (peaks of N-acetylaspartic acid). Conclusion We suggest using MRS to detect N-acetylaspartic acid as an acceptable method for the diagnosis of Canavan’s disease in infants even with normal serum and urine N-acetylaspartic acid levels. References Adornato BT, O’Brien JS, Lampert PW, Roe TF, Neustein HB. Cerebral spongy degeneration of infancy. A biochemical and ultrastructural study of affected twins. Neurology 1972;22(2):202-10. Banker BQ, Robertson JT, Victor M. Spongy Degeneration of the Central Nervous System in Infancy. Neurology 1964; 14:981-1001. Chou SM, Waisman HA. Spongy Degeneration of the Central Nervous System: Case of Homocystinuria. Arch Pathol 1965; 79:357-63. Divry P, Vianey-Liaud C, Gay C, Macabeo V, Rapin F, Echenne B. N-acetylaspartic aciduria: report of three new cases in children with a neurological syndrome associating macrocephaly and leukodystrophy. J Inherit Metab Dis 1988; 11(3):307-8. Feigenbaum A, Moore R, Clarke J, Hewson S, Chitayat D, Ray PN, et al. Canavan disease: carrier-frequency determination in the Ashkenazi Jewish population and development of a novel molecular diagnostic assay. Am J Med Genet A 2004;124a(2):142-7. Hagenfeldt L, Bollgren I, Venizelos N. N-acetylaspartic aciduria due to aspartoacylase deficiency--a new aetiology of childhood leukodystrophy. J Inherit Metab Dis 1987; 10(2):135-41. Ishiyama G, Lopez I, Baloh RW, Ishiyama A. Canavan’s leukodystrophy is associated with defects in cochlear neurodevelopment and deafness. Neurology 2003; 60(10):1702-4. Janson CG, Kolodny EH, Zeng BJ, Raghavan S, Pastores G, Torres P, et al. Mild-onset presentation of Canavan’s disease associated with novel G212A point mutation in aspartoacylase gene. Ann Neurol 2006; 59(2):428-31. Kaul R, Gao GP, Aloya M, Balamurugan K, Petrosky A, Michals K, et al. Canavan disease: mutations among Jewish and non-Jewish patients. Am J Hum Genet 1994; 55(1):34-41. Kaul R, Gao GP, Balamurugan K, Matalon R. Cloning of the human aspartoacylase cDNA and a common missense mutation in Canavan disease. Nat Genet 1993; 5(2):118-23. Kvittingen EA, Guldal G, Borsting S, Skalpe IO, Stokke O, Jellum E. N-acetylaspartic aciduria in a child with a progressive cerebral atrophy. Clin Chim Acta 1986;158(3):217-27. Mahloudji M, Daneshbod K, Karjoo M. Familial spongy degeneration of the brain. Arch Neurol 1970; 22(4):294-8. Matalon R, Kaul R, Casanova J, Michals K, Johnson A, Rapin I, et al. SSIEM Award. Aspartoacylase deficiency: the enzyme defect in Canavan disease. J Inherit Metab Dis 1989; 12(Suppl 2):329-31. Matalon R, Michals K, Sebesta D, Deanching M, Gashkoff P, Casanova J. Aspartoacylase deficiency and N-acetylaspartic aciduria in patients with Canavan disease. Am J Med Genet 1988; 29(2):463-71. Morcaldi L, Salvati G, Giordano GG, Guazzi GC. Congenital familial spongy idiocy (van Bogaert-Bertrand syndrome) in a non-Jewish family (study of a 2d Italian family)]. Acta Genet Med Gemellol (Roma) 1969; 18(2):142-57. Ozand PT, Gascon GG, Dhalla M. Aspartoacylase deficiency, and Canavan disease in Saudi Arabia. Am J Med Genet 1990; 35(2):266-8. Schmidt H, Rott HD, Neuhauser G, Neumann W. [Spongious cerebral dystrophy at an infant age (Canavan-Bogaert-Bertrand types) in three siblings of a non-Jewish family in upper Franconia (author’s transl)]. KlinPadiatr 1978; 190(6):580-5. Shaag A, Anikster Y, Christensen E, Glustein JZ, Fois A, Michelakakis H, et al. The molecular basis of Canavan (aspartoacylase deficiency) disease in European non-Jewish patients. Am J Hum Genet 1995; 57(3):572-80. Sistermans EA, de Coo RF, van Beerendonk HM, Poll-The BT, Kleijer WJ, van Oost BA. Mutation detection in the aspartoacylase gene in 17 patients with Canavan disease: four new mutations in the non-Jewish population. Eur J Hum Genet 2000; 8(7):557-60. Toft PB, Geiss-Holtorff R, Rolland MO, Pryds O, Muller-Forell W, Christensen E, et al. Magnetic resonance imaging in juvenile Canavan disease. Eur J Pediatr 1993; 152(9):750-3. Michals K, Matalon R. Canavan’s disease. In: Raymond GV, Eichler F, Fatemi A, Naidu S, eds. Leukodystrophies. London: Mac Keith Press.2011.P.156-69. Breitbach-Faller N, Schrader K, Rating D, Wunsch R. Ultrasound findings in follow-up investigations in a case of aspartoacylase deficiency (Canavan disease). Neuropediatrics 2003; 34:96–9. Matalon RM, Michals-Matalon K. Spongy degeneration of the brain, Canavan disease: biochemical and molecular findings. Front Biosci 2000; 5:D307–11. Matalon R, Michals K, Kaul R. Canavan disease: from spongy degeneration to molecular analysis. J Pediatr 1995; 127:511–7. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->